Row orientation effects on Syrah grapevine performance during winter growing season - de Souza, Claudia Rita; Vieira da Mota, Renata; Pinheiro Carvalho Silva, Camila; Paulino Raimundo, Ricardo Henrique; de Paula Fernandes, Fernanda; Peregrino, Isabela (Revista Ceres, 2025)
The sunlight and heating effects on leaves and grapes are directly influenced by row orientation in vineyards. Row orientation studies have not been addressed under double pruning management, a technique used to transfer the wine grape harvest from wet summer to dry winter season in Brazilian Southeast. Effects of grapevine row orientation (north/south – NS and east/west – EW) of vertically trellised and shoot positioned Vitis vinifera L. Syrah grafted onto 1103 Paulsen were investigated in the South of Minas Gerais State. The vegetative vigor was increased in NS oriented vines, probably due to high photosynthesis as suggested by the highest leaf starch accumulation. The leaf and stem water potential were slight affected by row orientation. NS orientation increased the cluster weight, but cluster number and yield per vine were not affected by treatments. Berries from NS oriented vines also showed the highest values of anthocyanins and total phenols. Under NS orientation there was a reduction on tartaric acid and soluble sugar in berries probably diluted by increased cluster weight. This study showed that vineyard under NS orientation improved grapevine vigor and promoted better phenolic maturity in wine grapes harvested during the winter season than EW orientation.